LEAF ANATOMY OF FREYCINETIA JAVANICA BLUME AND FREYCINETIA SCANDENS GAUDICHAUD (PANDANACEAE, FREYCINETOIDEAE) - Yessy Santika (Floribunda, 2010)
Yessy Santika 2010. Leaf Anatomy of Freycinetia javanica Blume and Freycinetia scandens Gaudichaud (Pandanaceae; Freycinetoideae). Floribunda 4(1): 18–20. — Leaf anatomy of Freycinetia javanica and F. scandens differs in the arrangement of stomata and the shape of the cuticles. The leaf anatomy also supports the placement of the two species into two separate sections (Cyrtopoda for F. javanica, Oligostigma for F. scandens).